Abnormal Temperature and Bias Dependence of Threshold Voltage Instability in p-GaN/AlGaN/GaN HEMTs - Myeongsu Chae; Ho-Young Cha; Hyungtak Kim (IEEE Journal of the Electron Devices Society)
In this work, we investigated the instability of threshold voltage (Vth) in p-GaN/AlGaN/GaN high electron mobility transistors (HEMTs) under positive gate biases and high temperatures. We reveal an abnormal temperature dependence of threshold voltage instability, suggesting that threshold voltage instability significant differences at elevated temperatures and is primarily attributed to the trapping/detrapping of charged carriers. Notably, the positive shift in threshold voltage diminished and eventually reversed at low gate bias as the temperature increased. In contrast, the negative shift intensified with increasing temperature but began to mitigate above 100°C at high gate bias due to an enhanced de-trapping process of electrons and holes. These results suggest the presence of multiple mechanisms behind the threshold voltage instability under varying thermal conditions.